2012
DOI: 10.1074/mcp.m112.019463
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of O-GlcNAc-modified Proteins in Published Large-scale Proteome Data

Abstract: The attachment of N-acetylglucosamine to serine or threonine residues (O-GlcNAc) is a post-translational modification on nuclear and cytoplasmic proteins with emerging roles in numerous cellular processes, such as signal transduction, transcription, and translation. It is further presumed that O-GlcNAc can exhibit a site-specific, dynamic and possibly functional interplay with phosphorylation. OGlcNAc proteins are commonly identified by tandem mass spectrometry following some form of biochemical enrichment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 31 publications
3
59
1
Order By: Relevance
“…We next queried whether these 1,286 protein sequences might not only be substrates of kinases and OGT but also might display interplay in between phosphorylation and O-GlcNAcylation, whereby phosphorylation at P−3 in this consensus sequence should prevent O-GlcNAcylation. In support of our hypothesis, a few of these protein sequences have already been reported to be involved in phosphorylation/O-GlcNAcylation crosstalk [e.g., in the eIF4 that plays a role in mRNA translation (24) and the paired amphipathic helix protein Sin3a that acts cooperatively with OGT to repress transcription (25,26)]. …”
Section: Resultssupporting
confidence: 51%
“…We next queried whether these 1,286 protein sequences might not only be substrates of kinases and OGT but also might display interplay in between phosphorylation and O-GlcNAcylation, whereby phosphorylation at P−3 in this consensus sequence should prevent O-GlcNAcylation. In support of our hypothesis, a few of these protein sequences have already been reported to be involved in phosphorylation/O-GlcNAcylation crosstalk [e.g., in the eIF4 that plays a role in mRNA translation (24) and the paired amphipathic helix protein Sin3a that acts cooperatively with OGT to repress transcription (25,26)]. …”
Section: Resultssupporting
confidence: 51%
“…Spectra were labeled by pLabel with 20 ppm tolerance for fragment ions (27). GlcNAc specific reporters were also labeled (126.05495, 138.05495, 144.06551, 168.06552, 186.07608, 204.08665) (28).…”
Section: Methodsmentioning
confidence: 99%
“…Data Analysis-The mass spectrometric data were processed essentially as described (6). The data processing with Mascot Distiller 2.4.2.0 (Matrix Science, London, UK) was slightly modified to account for the particular fragmentation behavior of O-GlcNAc-6-phosphate peptides.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the interplay between O-GlcNAcylation and phosphorylation modulates the stability and activity of p53 (5). However, recent data revealed the frequent co-occurrence of O-GlcNAc and phosphate at proximal sites (6), suggesting the reciprocal regulation by O-GlcNAcylation and phosphorylation may not be a very general mechanism. Moreover, it has also been found that the distribution of O-GlcNAc sites relative to phosphorylation sites is rather random and that the modification rates at sites detected with both modifications are almost equal, indicating that, on a global level, the substrate recognition of both pathways is not interconnected (7).…”
mentioning
confidence: 98%
See 1 more Smart Citation